The Quality Of Remo Gagrag Anyar Dance Movements In The Art Performances Of Deaf People - selis, selis adi miftahul amin putri sarjuni; Bella, Bella Sintafiana Rachman; Djoko, Dr. Rohmat Djoko Prakosa S.Sn., M.Sn. (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2024)
The many platforms for performing arts for children with special needs provided by the government provide opportunities for them to express themselves through the arts, as well as promote social inclusion and community acceptance of the diversity of individual abilities. Different and unique learning methods make the author interested and want to know the quality of their movements in dance. Deaf people are the main object of this research. By using codes, they are able to dance traditional dances such as Remo Gagrag Ayar Dance. This thesis examines the quality of movement in deaf individuals using La Meri's theory of the basic elements of dance. These elements include space, energy, and time, which are used as a framework to evaluate movement quality in the context of deaf individuals. La Meri's theory provides a foundation for understanding how deaf people are able to develop their movement expression despite different sensory challenges. The research also integrates Merleau-Ponty's theory of the body, which challenges the common view that a perfect body is a complete body. By focusing on bodily experience and sensory perception, this thesis reveals how deaf people can change perceptions about their movement abilities and artistic expression.